Pembelajaran berasaskan inkuiri dalam meningkatkan kemahiran literasi sains dan pencapaian murid menerusi persekitaran pembelajaran dalam talian - Saupian, Yazid (2021)
This study was conducted to examine the effect of inquiry-based learning through the 5E model towards student's science literacy skills and student achievement through the online learning environment which is Google Classroom application for Science subjects. A quantitative research design, preexperimental study of a one group pre and post-test method was adopted in this study. The data collection process took about four weeks where a total of 30 students were selected as the sample of this study. The sample of this study consisted of Year 6 students selected through purposive sampling technique. Data were obtained through several instrum ents such as questionnaire, checklist forms and pre and post-tests that covers the topic “Force and Friction”. Data were analyzed using descriptive analysis and inferential analysis which is paired sanple t-test test using SPSS software. Findings of the study found that the level of readiness is at a satisfactory level where 63% of students agreed that online learning benefits them. The findings also found that students' Science literacy skills are encouraging where 80% of students showed that they can focus on completing assignments after going through an inquiry-based learning environment in the Google Classroom application. Finally, the study also dem onstrates that there is a significant difference between pre and post-test average scores in student Science achievement. In conclusion, through this study, researchers found that inquiry-based learning through the 5E model can improve student's Science literacy skills and Science learning achievement through Google Classroom application.